1999
DOI: 10.1258/1357633991932414
|View full text |Cite
|
Sign up to set email alerts
|

Patient cost–benefit analysis of teledermatology measured in a randomized control trial

Abstract: A randomized controlled trial of the costs and benefits of teledermatology consultations compared with traditional hospital consultations was carried out. Over a nine-month period, 197 patients were referred from general practice for a dermatological opinion, 98 for a teledermatology consultation and 99 for a hospital consultation. Eighty patients required an additional subsequent hospital appointment. Patients were asked to complete an economic questionnaire after each consultation, and 164 questionnaires wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 4 publications
4
32
0
1
Order By: Relevance
“…[3][4][5][6][7][8] Store-and-forward teledermatology using digital cameras has also recently been associated with reduced patient wait times, high patient satisfaction, [9][10][11][12][13] promising diagnostic reliability, [14][15][16][17] and clinical outcomes similar to conventional, faceto-face clinical care. 18,19 To date, however, the vast majority of teledermatology studies and projects have focused on industrialized nations, whereas the potential need for teledermatology may be most profound in the developing world.…”
mentioning
confidence: 99%
“…[3][4][5][6][7][8] Store-and-forward teledermatology using digital cameras has also recently been associated with reduced patient wait times, high patient satisfaction, [9][10][11][12][13] promising diagnostic reliability, [14][15][16][17] and clinical outcomes similar to conventional, faceto-face clinical care. 18,19 To date, however, the vast majority of teledermatology studies and projects have focused on industrialized nations, whereas the potential need for teledermatology may be most profound in the developing world.…”
mentioning
confidence: 99%
“…For example, researchers in New Zealand found that, compared to a clinic visit, the use of LI teledermatology saved patients an average of 3.45 hours of time, primarily due to reduced traveling time (Oakley et al, 2000). However, LI teledermatology does not necessarily reduce consult time for the dermatologist (Loane et al, 1999(Loane et al, , 2001bOakley et al, 2000).…”
Section: Clinical Outcomes For LI Teledermatologymentioning
confidence: 99%
“…Diese sog. "live interactive"-Konsultation bietet den Vorteil der unmittelbaren aktiven Kommunikation, ist aber zeitaufwendiger [24]. Zum einen müssen zwischen Sender und Empfänger genaue…”
Section: Bildübertragungunclassified